Alih Teknologi Pembuatan Lunas Baja Bagi Pengrajin Kapal Kayu Tradisonal di Kelurahan Galesong Kota, Kecamatan Galesong, Kabupaten Takalar - Ganding Sitepu; M.R. Firmansyah; Misliah -; W. Djafar; Rosmani -; Suandar Baso; Akbar Asis; A. Rahmat Darwis (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
South Sulawesi is known as a place for wooden shipbuilding. The main problem faced by craftsmen is the shortage of wood. The solution, proposed the use of steel as the keel of the ship. In collaboration with the wooden boat craftsman group "Patorani" in Galesong District, Takalar Regency, an activity was held to transfer technology for making steel as a wooden ship keel. The main goal is that steel which is accepted as a wooden ship keel material, so that the shortage of wood can be substituted with steel. As a result, the belief that the wooden keel of the ship can be replaced with steel. Substitution of ship keel material with steel material based on the theory of structural strength. Activity’s outcomes are identifyed by the perceptions of the craftsmen and the views of the craftsmen. The results showed that before the activity, 90% of the crafters had heard of and were not sure that the ship's keel could be made of steel. After the socialization and demonstration activities, it turned out that only one out of 15 participants still doubted that ships were made of steel. The conclusion of this activity is that the craftsmen are ready to apply the innovative technology of replacing wooden keels with steel materials.